Timely linkage of individuals to substance use disorder treatment: development, implementation, and evaluation of FindHelpNowKY.org - Terry Lee Bunn; Dana Quesinberry; Tyler Jennings; Amber Kizewski; Heather Jackson; Sarah McKee; Sarah Eustice (BMC, 2019)
Abstract Background Substance use disorders (SUD) have steadily increased over the last two decades. Seeking SUD treatment involves searching SUD treatment facility types (inpatient, outpatient and intensive outpatient, residential and family residential, and detoxification facilities) that offer specialized SUD treatment depending on individual needs and preferences. Referrals to SUD treatment require innovative strategies that rapidly link individuals to SUD treatment when they are at the critical stage of readiness. The aim of this study was to develop, implement, and evaluate a user-friendly SUD treatment facility opening availability website called FindHelpNowKY.org. The objectives of the study were to 1) recruit SUD treatment facility and partner participation; 2) develop platform, content, and analytics for the FindHelpNowKY.org website intervention with an information repository; 3) assess barriers and facilitators to implementation; and 4) evaluate the development and implementation of FindHelpNowKY.org. Methods Website development stakeholders were identified and the website concept was developed. The logic model for FindHelpNowKY.org outlined resources, activities, and outputs as well as the associated short-term, medium-term, and long-term objectives, along with a website evaluation plan. Website usability and focus group testing was conducted. Information repository resource documents were compiled and categorized. An inventory of Kentucky-based SUD treatment facilities was compiled using various state and federal resources. Results Development/implementation barriers were addressed, facilitators were identified, and the website was implemented; 83% of SUD treatment facilities were indexed on the website, and average website user time was 7 min. From February to October 2018, there were 29,000 visitors, and 30,000 unique searches. The most common website query was a friend or family member seeking long-term residential or outpatient treatment facilities accepting Medicaid or Medicare. Conclusions FindHelpNowKY.org has the potential to fill a critical need for timely access to available SUD treatment in the state. The website may be a valuable resource for health professionals that can enhance clinical workflow and reduce staff time conducting phone and website searches for available SUD treatment. The website is a promising tool for assessing current SUD treatment capacity vs. SUD treatment need. The FindHelpNow model can be used by other states to increase timely access to SUD treatment.